Visualizing the blast-induced stress wave and blasting gas action effects using digital image correlation. (December 2018) - Yang, Renshu; Ding, Chenxi; Yang, Liyun; Lei, Zhen; Zhang, Zhaoran; Wang, Yanbing
Abstract: Rock blasting fragmentation is a result of the combined action of a blast-induced stress wave and the blasting gas. Incorporating high-speed camera technology, an experimental system of high-speed digital image correlation is established and is extended to blasting research. Using two-dimensional model experiments, the action effects of a blast-induced stress wave and blasting gas on the formation of the crush and fracture zones are studied, and the blasting attenuation law in the elastic vibration zone is also analyzed. The results show that the blast-induced stress wave and the blasting gas are respectively the main driving forces for the crush zone and fracture zone formation. The effect of the blasting gas reduces the crush zone size and increases the crack propagation length as well as the medium's stress peak. In the elastic vibration zone, the radial and circumferential stress of the medium are both first compressive and then tensile. The radial and circumferential stress are respectively dominated by compressive and tensile stress, and the radial stress decays more rapidly. With increased distance from the borehole, the medium's stress state gradually turns from mainly circumferential tensile to mainly radial compressive. In addition, in decoupled charge blasting, the stress attenuation index shows a trend of initially increasing and then decreasing with the increase of the decoupling coefficient. Compared with the attenuation of the circumferential stress, the air filling in the decoupled charge blasting more significantly affects the radial stress attenuation.